PROSES PENGELOLAAN PEMBELAJARAN AL-QUR’AN DI TPQ AN-NAJAH - BudiHarti; Maulida Nurul Azmi (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
The Al-Qur’an Education Park (TPQ) is an educational institut in terms of material and pattern his education. The special material focuses on teaching reading the Qur’an with good and correct or in accordance with the rules of recitation of tajwid or usual with reading tartil and practice prayer, pray, and writing. The establishment of TPQ as evidence of the desire of Muslims to improve faith and Islam in the mastery and deepeing of the holybook. This research using qualitative methods by conducting interviews dan documentation. Data and sources the data in this study are in the form of primary data and secondary data. Based on the results of interviews, it was revealed that management of TPQ was very efficiently. This indicated by TPQ head’s statement that the management at TPQ An-Najah is very good and follows the standard TPQ, which is as much by 20% increase in the of children attending in this TPQ. The purpose of the establishing of TPQ is to build citizens so that they have a Muslim personality according to with the teachings of Islam and instill that religious in life.